Ear Abuse among School Children in Ekiti, Nigeria - Olajide, Toye Gabriel; Olajuyin, Oyebanji Anthony; Eletta, Adebisi Paul; Dosunmu, Adepeju Oluwatona (International Journal of Innovative Research in Medical Science, 2018)
Background/Aim: Otological trauma due to physical abuse is a common occurrence among the young persons. However, the condition is overlooked and underreported. This study aimed at determines prevalence and profile of ear abuse in school children in Ekiti, Nigeria. Methodology: This study was a cross sectional survey among secondary school students in Ekiti, South Western Nigeria. Data were collected using a semi-structured interviewer administered questionnaire. Results: A total of 130 students aged 13 and 16 years participated in the survey. Of the 130 students that were interviewed, 76 (58.5%) had been otologically abused (Slapped) at one time or the other. Majority (26.9%) of the students were slapped by their parents. Left ear was mostly affected in 39 (51.3%) of them. The most common reason for the slap was disobedience in 56 (73.7%) of the students. Only 5.4% reported the case of slap to appropriate authority. About 73.7% did not receive treatment or any form of intervention. Pure tone audiogram (PTA) done showed that 32.9% (19.7 % male and 13.2 % female) of the respondents had mild conductive hearing loss. Conclusion: Ear abuse, although poorly recognized and underreported is still common in our society. A prevalence of 58.4 % with 32.9% hearing loss was recorded in this study. There is need for a public enlightenment programs in order to create awareness among teachers, school managers and parents so as to address these ugly trends and to prevent late sequel of hearing loss and learning disability.